2015
DOI: 10.1515/lp-2015-0002
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between prosodic weakening and sound change: evidence from the German tense/lax vowel contrast

Abstract: Abstract:The study tests a model of sound change based on how prosodic weakening affects shortening in polysyllabic words. Twenty-nine L1-German speakers produced minimal pairs differing in vowel tensity in both monosyllables /zakt, zaːkt/ and disyllables /zaktə, zaːktə/. The target words were produced in accented and deaccented contexts. The duration ratio between the vowel and the following /kt/ cluster was less for lax than tense vowels and less for disyllables than monosyllables. Under deaccentuation, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 46 publications
(48 reference statements)
0
11
0
Order By: Relevance
“…Bang, Sonderegger, Kang, Clayards, and Yoon (2015) found that both VOT merger and f0 enhancement in the Seoul lenis-aspirated contrast disproportionately affect high-frequency words (which tend to be hypo-articulated or reduced). Similarly, Harrington, Kleber, Reubold, and Siddins (2015) found that the German tense-lax vowel distinction is more merged when de-accented (also a context for hypoarticulation), and thus more likely to induce misperception. Examination of different speech styles more likely to show hypoarticulation might therefore reveal an incipient change in Hunchun production.…”
Section: Perceptual Cue-weighting In the Context Of Sound Changementioning
confidence: 86%
“…Bang, Sonderegger, Kang, Clayards, and Yoon (2015) found that both VOT merger and f0 enhancement in the Seoul lenis-aspirated contrast disproportionately affect high-frequency words (which tend to be hypo-articulated or reduced). Similarly, Harrington, Kleber, Reubold, and Siddins (2015) found that the German tense-lax vowel distinction is more merged when de-accented (also a context for hypoarticulation), and thus more likely to induce misperception. Examination of different speech styles more likely to show hypoarticulation might therefore reveal an incipient change in Hunchun production.…”
Section: Perceptual Cue-weighting In the Context Of Sound Changementioning
confidence: 86%
“…Since coarticulation and duration are negatively correlated, this analysis predicts that duration would decrease as a function of the number of syllables in a word for children. As such, the children's productions would reflect the phenomenon of Compensatory Shortening (also known as polysyllabic shortening), or the tendency for segment durations to shorten in longer-duration and/or polysyllabic words (Harrington et al 2015;Lehiste & Shockey 1972;Munhall et al 1992).…”
Section: Compensatory Shorteningmentioning
confidence: 99%
“…One additional difference between the adults and children was that children compensated for word length by shortening the duration of their VC sequences in longer words (or, variably, lengthening duration in the shorter words). This phenomenon is known as compensatory shortening (Harrington et al 2015;Lehiste 1972;Munhall et al 1992). 17 While children demonstrated a tradeoff in sequence duration and prosodic word size, adults were insensitive to word size.…”
Section: Compensatory Shorteningmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the ubiquity of this shift, it remains unclear exactly how it takes place. Presumably, some listener/learner needs to arrive at a novel parse of the signal, either due to error [14], mode of perception [15], or ambiguity of the coarticulatory source [16,17]. This leads us to ask if there are contexts in which the salience of microprosodic cues might increase or even come to dominate the perceptual parse.…”
Section: Introductionmentioning
confidence: 99%